How Did They Grow: An Intervention to Reduce Stunted Growth in Low‐Income Mexican‐American Children. Issue 2 (24th February 2016) - Reifsnider, Elizabeth; Shin, Cha‐Nam; Todd, Michael; Jeong, Mihyun; Gallagher, Martina; Moramarco, Michael
Abstract: Growth stunting is a complex phenomenon related to undernutrition that can contribute to developmental delay, cognitive deficits, and small size and obesity in adulthood. Stunted growth, defined as height for age below the 5th percentile, is primarily caused by chronic malnutrition. In this study, a community‐based intervention to reduce undernutrition was tested in a quasi‐experimental design with 174 low‐income, Mexican‐American mothers and children recruited from a Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) clinic in a major southwestern city. The intervention was based on the public health nursing practice of collaborating with mothers of young children on appropriate nutrition and parenting, and was tailored by the author and community informants for mothers of children with stunted growth. Data were collected on child height and weight, dietary intake, maternal acculturation, maternal perceived stress as measured by the Perceived Stress Scale (PSS), home environment as measured by the home screening questionnaire (HSQ), and maternal–child interaction as measured by the Nursing Child Assessment Teaching Scale (NCATS). Intervention children had higher growth velocity than the children in the comparison group. These findings were especially prominent for children of women who were older and less acculturated. Results suggest that a nursing intervention delivered in collaboration with WIC can make a significant improvement in growth of low‐income children with growth stunting. © 2016 Wiley Periodicals, Inc.